Strengthening Pancasila in Religious Life: Pioneering a New Form of Relations between Islam and Pancasila - Ma'mun Murod; Ali Noer Zaman; Djoni Gunanto; Usni Usni (Journal of Government and Civil Society, 2022)
This article has the main discussion on the relationship between Islam and Pancasila. This article aims to find out more about the opinions of Islamic mass organizations leaders about the relationship between Islam and Pancasila. In addition, this article aims to map the views and thoughts of religious leaders about Pancasila in religious life. This article uses explorative interpretive quantitative and qualitative methods. Quantitative data was collected by surveying 40 Muhammadiyah figures, 40 NU figures, and 20 other Islamic mass organizations. The survey was conducted randomly on the figures of Islamic organizations with a random selection of respondents at the national and provincial levels. This survey uses purposed random sampling. This study describes and explains a phenomenon that occurs by using an interpretive understanding approach to reality or the object of research. Through this study it was found that as many as 21% of respondents strongly agree and 79% agree that Pancasila is the basis of the state. Although support for Pancasila as the state ideology is very high, in the related survey there are inconsistencies, namely as many as 33% still crave the presence of the Jakarta Charter in the constitution, while 67% reject related matters. In general, this article argues that the relationship between Islam and Pancasila today is better than before because the majority of Muslims have accepted Pancasila as the basis of the state constitution. it was found that as many as 21% of respondents strongly agree and 79% agree that Pancasila is the basis of the state. Artikel ini memiliki pembahasan utama tentang hubungan antara Islam dan Pancasila. Artikel ini bertujuan untuk mengetahui lebih jauh tentang pendapat para tokoh ormas Islam tentang hubungan Islam dan Pancasila. Selain itu, artikel ini bertujuan untuk memetakan pandangan dan pemikiran para pemuka agama tentang Pancasila dalam kehidupan beragama. Artikel ini menggunakan metode kuantitatif dan kualitatif interpretatif eksploratif. Data kuantitatif dikumpulkan dengan mensurvei 40 tokoh Muhammadiyah, 40 tokoh NU, dan 20 tokoh ormas Islam lainnya. Survei dilakukan secara acak terhadap tokoh-tokoh ormas Islam dengan pemilihan responden secara acak di tingkat nasional dan provinsi. Survei ini menggunakan purposed random sampling. Penelitian ini mendeskripsikan dan menjelaskan suatu fenomena yang terjadi dengan menggunakan pendekatan pemahaman interpretative terhadap realitas atau objek penelitian. Melalui penelitian ini ditemukan bahwa sebanyak 21% responden sangat setuju dan 79% setuju bahwa Pancasila adalah dasar negara. Meski dukungan terhadap Pancasila sebagai ideologi negara sangat tinggi, dalam survei terkait terdapat inkonsistensi, yakni sebanyak 33% masih mendambakan kehadiran Piagam Jakarta dalam konstitusi, sedangkan 67% menolak hal terkait. Secara umum, artikel ini berpendapat bahwa hubungan Islam dan Pancasila saat ini lebih baik dari sebelumnya karena mayoritas umat Islam telah menerima Pancasila sebagai dasar konstitusi negara. Ditemukan bahwa sebanyak 21% responden sangat setuju dan 79% setuju bahwa Pancasila adalah dasar negara.